AKTIVITAS SEKTOR INFORMAL PADA MALAM HARI ( Studi Kasus Pembeli dan Pedagang Jagung Bakar Di Jalan Naga Sakti Stadion Utama Riau Pekanbaru ) - Marito Manurung; T. Romy Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This Research is being conduct in Jalan Naga Sakti Stadion Utama Riau Pekanbaru with purpose of gaining an information about the informal sector at the end of the day. The problems are (1) How is a profile of a street roasted corn seller in Jalan Naga Sakti, Pekanbaru Riau ? (2) How is the behavior of roasted corn visitor in Jalan Naga Sakti Pekanbaru Riau? The title of this research is " The Activity of Informal Sector At Night ( Legal studies of Buyer and Roasted Corn Seller in Jalan Naga Sakti Stadion Utama Riau Pekanbaru ) . This research is a qualitative research which being analyzed descriptively. Theory being used in this research is informal sector, street vendors, behaviours and social action. In this very research there is approximately 9 respondents. The technics that being used to get a sample are Purposive sampling and Accidental sampling. The results from the field say that the profile of roasted corn merchants differ from each other, ranging from selling, selling hours to facilities provided by traders and the behavior of visitors also show deviant behavior in which visitors come to kiss with their partners.Key words : Roasted Corn Seller, Visitors, Deviant Behaviours